PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Selama Periode 2016-2019) - Rointan Silalahi; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2021)
The aim of this study are to examine the effect of corporate social responsibility and capital intensity to tax aggressiveness with firms size and profitability as a control variable. The population of this study manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2019. This study used purposive sampling method, with 276 total observation of sample. Multiple linear regression analysis is used in this study. The result of regression analysis showed that corporate social responsibility has insignificant effect on tax aggressiveness. But on the another hand, capital intensity has positive significant effect on tax aggressiveness.Size and profitability as a control variable has positive significant effect on tax aggressiveness.